2016
DOI: 10.1037/rep0000092
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological flexibility on life satisfaction and mood in muscle disorders.

Abstract: Impact and Implications-Psychological interventions offer a potential way to improve outcomes in MDs, which are progressive and mostly without disease modifying treatment. Yet, a dearth of a research using longitudinal designs means that we are unsure which psychological variables represent viable treatment targets in this context.-In line with the theoretical assumptions implicit in Acceptance and Commitment Therapy (ACT), this study suggests that psychological flexibility is a distinct process, which influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…These results nevertheless seem to argue against the results by Bjornsson and colleagues, which suggested that experiential avoidance did not predict depressive symptoms at 8 to 12 weeks later when depressive symptoms at baseline were entered as covariates. On the other hand, the current study goes in line with previous longitudinal studies on the effects of experiential avoidance on emotional well‐being in breast cancer, changes in anxiety and depression disorders, post‐traumatic stress disorder symptoms, pain disability and depressive symptoms in chronic pain due to whiplash, and life satisfaction in muscle disorders . This is aligned with the conceptualization of experiential avoidance as an important transdiagnostic process present in numerous mental health problems in several populations .…”
Section: Letter To the Editorsupporting
confidence: 89%
“…These results nevertheless seem to argue against the results by Bjornsson and colleagues, which suggested that experiential avoidance did not predict depressive symptoms at 8 to 12 weeks later when depressive symptoms at baseline were entered as covariates. On the other hand, the current study goes in line with previous longitudinal studies on the effects of experiential avoidance on emotional well‐being in breast cancer, changes in anxiety and depression disorders, post‐traumatic stress disorder symptoms, pain disability and depressive symptoms in chronic pain due to whiplash, and life satisfaction in muscle disorders . This is aligned with the conceptualization of experiential avoidance as an important transdiagnostic process present in numerous mental health problems in several populations .…”
Section: Letter To the Editorsupporting
confidence: 89%
“…It suggests that our ability to adopt a mindset that is open to our experience and awareness of how we are being influenced by internal and external stimuli will allow us to respond to adversity in ways that keep us engaged in meaningful life activities. This "open," "aware" and "engaged" mindset is known as psychological flexibility, and it has been found to be predictive of successful adjustment to a range of life experiences and mental and physical health conditions (Graham, Gouick, Krahé, & Gillanders, 2016;Hayes et al, 2006). Importantly, psychological flexibility can be improved through training and therapy, and so represents a modifiable target for psychological intervention.…”
mentioning
confidence: 99%
“…Traditional CBT may be most suitable for targeting illness perceptions, which have been shown to correlate with QoL and mood in MD (Graham et al, 2014). ACT instead targets psychological flexibility, which was found to predict QoL and mood in a previous longitudinal study with an MD population (Graham et al, 2016a). ACT has not yet been investigated in the context of MD.…”
Section: Acceptance and Commitment Therapymentioning
confidence: 99%